2012
DOI: 10.1097/ta.0b013e3182468b51
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the use and predictive value of “emergency medical services provider judgment” in out-of-hospital trauma triage

Abstract: Background “EMS provider judgment” was recently added as a field triage criterion to the national guidelines, yet its predictive value and real-world application remain unclear. We examine the use and independent predictive value of EMS provider judgment in identifying seriously injured persons. Methods We analyzed a population-based retrospective cohort, supplemented by qualitative analysis, of injured children and adults evaluated and transported by 47 EMS agencies to 94 hospitals in 5 regions across the W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
49
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 28 publications
4
49
1
Order By: Relevance
“…Emergency Medical Services provider judgment has been shown to be predictive of serious injury, even after accounting for other triage criteria. 38 Selective application of the guidelines, patient choice, EMS provider knowledge and training, provider beliefs, availability of EMS units, traffic, weather, and hospital proximity can also contribute to triage decision making.…”
Section: Discussionmentioning
confidence: 99%
“…Emergency Medical Services provider judgment has been shown to be predictive of serious injury, even after accounting for other triage criteria. 38 Selective application of the guidelines, patient choice, EMS provider knowledge and training, provider beliefs, availability of EMS units, traffic, weather, and hospital proximity can also contribute to triage decision making.…”
Section: Discussionmentioning
confidence: 99%
“…23 Another study also found that EMS provider judgment was frequently cited as a criterion for transport and was associated with a 23% increased odds of having a severe injury. 24 However, a literature review concluded that the evidence-base to support paramedic judgment as an accurate triage criterion is lacking. 25 Our model indicates that EMS providers routinely rely on their intuition to make destination decisions, but it is uncertain whether such judgment may have additional value independent of the FTDS.…”
Section: Discussionmentioning
confidence: 99%
“…“EMS provider judgment” was the most common triage criterion cited by EMS personnel across all regions, being used almost three times as often as the next most commonly cited criterion, even though one region (region A) did not use the criterion at all. The use and independent predictive value of EMS provider judgment in identifying patients with serious injuries 24 and the integral role of provider judgment in out-of-hospital cognitive processing for field triage 25 have been previously detailed. Closer evaluation of the one region not using the EMS provider judgment criterion revealed that the same region had disproportionate use of the “energy” criterion.…”
Section: Discussionmentioning
confidence: 99%